Community interest and feasibility of using a novel smartphone‐based formaldehyde exposure detection technology. Issue 4 (11th January 2018) - Castner, Jessica; Gehrke, Gretchen E.; Shapiro, Nicholas; Dannemiller, Karen C.
Abstract: Objective: This study is the first community engagement phase of a project to develop a residential formaldehyde detection system. The objectives were to conduct a feasibility assessment for device use, and identify factors associated with concerns about environmental exposure and community interest in this device. Design and Sample: A cross‐sectional, internet‐based survey employing community‐based participatory research principles was utilized. 147 individuals participated from a focused Waycross, Georgia (58.5%) and broader national sample (41.5%). Measures: Variables included acceptable cost and number of testing samples, interest in conducting tests, levels of concern over pollutants, health status, housing, and demographics. Results: The majority of participants desired a system with fewer than 10 samples at ≤15.00 per sample. Statistically significant higher levels of concern over air quality, formaldehyde exposure, and interest in testing formaldehyde were observed for those with overall worse health status and living in the Waycross, Georgia geographic region. Significant differences in formaldehyde testing interest were observed by health status (OR = 0.31, 95% CI = 0.12–0.81 for home testing) and geographic location (OR = 3.16, 95% CI = 1.22–8.14 for home and OR = 4.06, 95% CI = 1.48–11.12 for ambient testing) in multivariate models. Conclusions: Geographic location and poorer general health status were associated with concerns over and interest in formaldehyde testing.